DARI PUISI MANTRA HINGGA PUISI ESAI SEBUAH LANSKAP PERPUISIAN INDONESIA - Awla Akbar Ilma (Jurnal Penelitian Humaniora, 2016)
This research specially addresses through a sociological perspective the existence of narrative poetry that lately rampant in Indonesia. Therefore, this research assumes that the existence of a literary work is closely link with the condition of the time. Thisresearch seeks to compare with the kinds of poetry before as traditional poerty, poetry of pujangga baru, mantera poetry, and Mbeling poetry both aesthetic characteristics and social conditions. Based on the research process, it is known that the narrativepoerty has unique characteristics that are different from other types of poetry. It is known that narrative poetry is a real respond to assessment of poems that are considered difficult to understand. Therefore, this poetry tries to synergize with readers, making certain platforms, giving easy access to the meaning of the poetry. Thus sociological characteristics known as the effect of the conditions which always demanding the ease and speed. Such condition if drawn further was the effect of industrialization and technological pace.